PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP BEHAVIORAL INTENTION CALON GURU EKONOMI DALAM MENGGUNAKAN ALAT GAMIFIKASI (KAHOOT, QUIZIZZ, TIMETREE) - Sugiyantoro, Yoga; Andriansyah, Eka Hendi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This research aims to find out how Perceived Ease of Use and Perceived Usefulness influence the Behavioral Intention of Prospective Economics Teachers to Use Gamification Tools in their future teaching. This research uses a sample of 200 students from the State University in East Java. The analysis technique used in this research is Partial Least Squares (PLS) analysis using SmartPLS software version 4.0. The results of this research indicate that there is a significant influence between Perceived Ease of Use and Perceived Usefulness on the Behavioral Intention of Prospective Economics Teachers. These results prove that the two exogenous variables influence prospective teacher students' interest in using gamification tools.